Muddy foil: a history of extraction and resistance in the lower Mississippi River Delta. Issue 2 (3rd April 2021) - Randolph, Ned
ABSTRACT: This article considers Mississippi River Mud as an analytic for unruly ontologies and fugitive spaces. Historic discourses around mud—and by extension, muddy spaces—were mapped onto lawless, not-fully-humans who occupied them. They reflected efforts to impose rational order and naturalize a political economy of monoculture, river shipping, and fossil fuels. This episteme, which reduces complex ecologies to agents of capital extraction, has transformed the once alluvial forests and marshlands of south Louisiana into subsiding oil and gas fields, abandoned wells, and eroding canals. An explication of mud by communication scholars ruptures this discourse in imagining alternative ways of living.